Pengembangan Manajemen Menu Gizi Diet Kesehatan Berbasis VBA (Visual Basic For Aplications) Macro Excel - Effendy, Ibrahim Rully; Prihandini, Yustin Ari (Persatuan Dosen Kesehatan Masyarakat, 2024)
Public health has become a primary concern in the era of globalization and modernization. However, food consumption surveys in Indonesia indicate low consumption of fatty foods and fruits. Therefore, it is crucial to maintain a balanced diet. Despite offering healthy menus, GoodMeal Catering still relies on manual calculations. This research aims to integrate Visual Basic for Applications (VBA) into Microsoft Excel for designing daily diet menus. This method can assist individuals in planning menus that align with their nutritional needs. Data from the Indonesian Food Composition Table (TKPI) 2020 are used as a database to automatically fulfill macro and micro-nutritional requirements based on the composition of input food items. The result is an application that simplifies menu planning and efficient monitoring of nutrient intake for users. The integrity of TKPI data and collaboration with the Indonesian Ministry of Health provide a robust foundation in nutritional science for designing personalized diets that support health and prevent various diseases